Старшинський корпус Стародубського полку за доби гетьмана Івана Мазепи - Лаєвський, А. (Сiверянський лiтопис, 2015)
Стаття присвячена характеристиці козацько-старшинської спільноти Стародубського полку у період гетьманування Івана Мазепи. Досліджується участь старшини у суспільно-політичному житті Української козацької держави, реконструюється її
персональний склад, розглядається службова кар’єра окремих представників. Статья посвящена характеристике казацко-старшинской общности Стародубского полка в период гетманства Ивана Мазепы. Исследуется участие старшины в
общественно-политической жизни Украинского казацкого государства, реконструируется ее личный состав, рассматривается служебная карьера отдельных представителей. Ukrainian historiography has a respectful tradition in studying the wide circle of questions
connected with the personality of Hetman Ivan Mazepa and his surroundings. Despite that
fact, the history of local nobles (Ukrainian Starshyna) needs a deeper attention.
The article is dedicated to the characteristics of officer’s corps of Starodub regiment at
the time of Ivan Mazepa hetmaning. The attention is paid to studying the problem of their
participation in the political and social life of Ukrainian Cossack State, to reconstructing of
their personal roster and describing the serving career of most influential representatives.
The author makes a conclusion that Starodub nobles didn’t participate actively in political
life of Ukrainian Cossack State. They didn’t have the representation in the central authorities
and didn’t have the opportunity to influence the policy of Hetman. At the same time Hetmans
meaning the importance of Starodub lands sent their agents to the regiment for better check-up.
Starodub regiment and it’s officers as the military units were used at the time of Moscow-
Turkish war and the Great Northern War. During the last one led by colonel Ivan Skorapapdskyi
Starodub starshyna didn’t held up Hetman Ivan Mazepa and stayed loyal to Moscow tsar Piter I.
The article contains the appendix in which the author demonstrates the rosters of Starodub regimental officers, which were created based on the historical studies of predecessors and made good on some author’s material.